Perianal Paget's disease: a clinicopathological and immunohistochemical study of 13 cases - Xiaoyan Liao; Xiuli Liu; Xuemo Fan; Jinping Lai; Dongwei Zhang (BMC, 2020)
Abstract Background Perianal Paget's disease (PPD) is rare and mostly described in clinical literature as case reports or small series. Methods We investigated the clinicopathologic and immunohistochemical features of PPD in a total of 13 cases retrieved from multiple academic institutions. Results The median age at diagnosis was 75 (range 50-86) years. Males were predominant with a male to female ratio of 2.25:1. Four (30.8%) cases were classified as primary PPD due to lack of synchronous or metachronous underlying malignancies, while nine (69.2%) were classified as secondary PPD with concurrent invasive adenocarcinoma (n = 8) or tubular adenoma with high-grade dysplasia (n = 1). Immunohistochemically, there is no differential expression of CK7 or CK20 in Paget's cells between primary and secondary PPD; however, GCDFP-15 was only positive in primary PPD (3/3 vs. 0/6, P = 0.012), while CDX2 was only positive in secondary PPD (0/3 vs. 7/7, P = 0.008), suggesting different cell origin. All patients received local surgical resection with or without adjuvant therapy. After a median follow-up of 47 months, one patient with secondary PPD (7.7%) died of disease progression from underlying adenocarcinoma. Conclusions PPD occurs in elderly patients with male predominance and is frequently associated with underlying malignancies. Differential expression of CDX2 and GCDFP-15 may help distinguishing primary vs. secondary PPD, which is important for management as the presence of an underlying malignancy impacts clinical course and prognosis. Surgical excision remains the major treatment strategy for PPD. Long-term follow-up is required to monitor the disease recurrence and metastasis.